SENSORY AND NUTRITIONAL QUALITY OF SWEET RECIPES PREPARED USING DATES PALM JAGGERY - Nande, Dr. Prajakta Jayant (IJRDO-Journal of Applied Science, 2016)
Present study deals with preparation of experimental recipes like diamond cuts, sweet rice, sesame seeds laddoo & pumpkin kheer using dates palm jaggery. Control recipes were prepared using sugarcane jaggery. Sensory evaluation was carried out in three trials by six judges. Diamond cuts made using dates palm jaggery were highly accepted for all sensory attributes (perfect scores of 10). Appearance, colour, doneness & texture of experimental sweet rice & sesame seeds laddoo prepared using dates palm jaggery received identical mean scores (10 for very good) to that of control sweet rice & sesame seeds laddoo prepared using sugarcane jaggery. Experimental pumpkin kheer prepared with dates palm jaggery was significantly rated above control pumpkin kheer prepared with sugarcane jaggery for appearance & colour (t=5.88, p<0.01). All experimental recipes were found energy dense, good in carbohydrate, protein & fat.